The Effectiveness of Web-Based Mobile Learning for Mobile Subjects on Computers and Basic Networks in Vocational High Schools - Dony Novaliendry; Asrul Huda; LatifahAnnisa; Resti Rahmi Khairati Costa; Yudhistira; Fivia Eliza, (International Journal of Interactive Mobile Technologies (iJIM), 2023)
This research and development are motivated by the problem of limited learning resources on Computers and Basic Networks in SMK Negeri 2. This happens because no learning media attracts students' interest in learning. Therefore, the writer tries to design interesting learning media for students. This study aims to determine the validity, practicality and effectiveness of the design and manufacture of mobile learning media based on mobile web subjects for computer and basic networking subjects for class X TKJ SMK Negeri 2 Padang. This research uses the research & development method. The research subjects were 35 people. The research model used is the development research model (ADDIE model), with the development steps as follows. (1) Analyze, (2) design, (3) development, (4) Implementation, and (5) Evaluate. The results of the overall effectiveness test assessment of the effectiveness of Mobile Web-Based Mobile Learning on Computers and Basic Networks (KJD) Class X SMK Negeri 2 Padang Odd Semesters of 93.57% so that the level of effectiveness can be interpreted very effectively used. In conclusion, based on the assessment and expert input and the results of the field trial of Mobile Web-Based Mobile Learning Media as a learning medium, it has been tested for feasibility and excellence. It can be used in the learning process on KJD subjects for class X TKJ SMK N 2 Padang.